2002
DOI: 10.1073/pnas.152094799
|View full text |Cite
|
Sign up to set email alerts
|

R9AP, a membrane anchor for the photoreceptor GTPase accelerating protein, RGS9-1

Abstract: The regulator of G protein signaling (RGS)-9-1⅐G␤5 complex forms the GTPase accelerating protein for G␣t in vertebrate photoreceptors. Although the complex is soluble when expressed in vitro, extraction of the endogenous protein from membranes requires detergents. The detergent extracts contain a complex of RGS9-1, G␤5, G␣t, and a 25-kDa phosphoprotein, R9AP (RGS9-1-Anchor Protein). R9AP is encoded by one intronless gene in both human and mouse. Full or partial cDNA or genomic clones were obtained from mice, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
150
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(156 citation statements)
references
References 48 publications
6
150
0
Order By: Relevance
“…The function of this unique sequence is still unknown. However, some data suggested its importance in the interactions of RGS9-1 with targets (10,17,65). As highlighted in the sequence alignment (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The function of this unique sequence is still unknown. However, some data suggested its importance in the interactions of RGS9-1 with targets (10,17,65). As highlighted in the sequence alignment (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…RGS9-1 also forms a complex with a 25-kDa photoreceptor-specific phosphoprotein, RGS9-1 anchor protein (R9AP). R9AP binds to the N-terminal domain of RGS9-1 and anchors RGS9-1 to the disk membrane (17).…”
mentioning
confidence: 99%
“…On the other hand, binding of monomeric RGS7 in vitro to G␣ o -GDP has been detected in a pull-down assay, where it was as high as 50% that in the presence of aluminummagnesium-fluoride (5). The interaction between G␤5L⅐RGS9 and G␣t-GDP has also been shown (29). Earlier surface plasmon resonance studies of RGS16 and G␣t revealed that in the presence of ␥ subunit of cGMP phosphodiesterase the affinity of RGS16 to G␣t-GDP-aluminum-magnesium-fluoride is only 2-fold higher than to G␣t-GDP (30), also illustrating measurable interaction of some RGS proteins to G␣-GDP.…”
Section: Function Of G␤5⅐rgsmentioning
confidence: 99%
“…The R7-Gb5 association is essential for the protein's stability and function (He et al, 2000;Chen et al, 2003). R7 proteins also share a DEP domain (Martemyanov et al, 2003;Ballon et al, 2006), which is required for their interaction with the adaptor molecules R9AP in the retina (Hu and Wensel, 2002) and R7 family binding protein (R7BP) in the brain (Martemyanov et al, 2005). The R7-R7BP interaction is essential for the cellular localization and function of R7 proteins, as it determines the localization of the protein at the cell membrane (Drenan et al, 2005;Anderson et al, 2009;Jayaraman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%